2017
DOI: 10.1038/srep46400
|View full text |Cite
|
Sign up to set email alerts
|

First Characterisation of Volatile Organic Compounds Emitted by Banana Plants

Abstract: Banana (Musa sp.) ranks fourth in term of worldwide fruit production, and has economical and nutritional key values. The Cavendish cultivars correspond to more than 90% of the production of dessert banana while cooking cultivars are widely consumed locally around the banana belt production area. Many plants, if not all, produce Volatile Organic Compounds (VOCs) as a means of communication with their environment. Although flower and fruit VOCs have been studied for banana, the VOCs produced by the plant have ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Hence, (Z,E)-α-farnesene might be used as a putative marker to discriminate apple-fruit varieties for food authenticity purposes. The same applies in the case of linalool, which, in the banana study mentioned above, was only detected in Pacific plantain and, in the current study, was only identified in Branco fruit samples; this VOC showed insect- and disease-control properties [ 35 ], with benefits for the quality of apple fruits. Both linalool and estragole could differentiate basil varieties [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Hence, (Z,E)-α-farnesene might be used as a putative marker to discriminate apple-fruit varieties for food authenticity purposes. The same applies in the case of linalool, which, in the banana study mentioned above, was only detected in Pacific plantain and, in the current study, was only identified in Branco fruit samples; this VOC showed insect- and disease-control properties [ 35 ], with benefits for the quality of apple fruits. Both linalool and estragole could differentiate basil varieties [ 36 ].…”
Section: Discussionsupporting
confidence: 60%
“…In this sense, (Z,E)-α-farnesene was only identified in 2 varieties (Festa and Branco) about 100 times less than another isomer ((E,E)-α-farnesene) [ 34 ]. In this context, in a previous study, (Z,E)-α-farnesene was able to differentiate banana plant cultivars since this VOC was detected in the Pacific plantain cultivar, but not identified in Cavendish cultivar, whereas (E,E)-α-farnesene was detected in both banana cultivars [ 35 ]. Hence, (Z,E)-α-farnesene might be used as a putative marker to discriminate apple-fruit varieties for food authenticity purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Volatiles from the aboveground part of B. juncea were collected after 8 weeks of growth in the greenhouse through a “push-pull” system previously reported by Berhal et al . Briefly, air was pushed through charcoal active powder (AR, Suzhou Xinqing Technology Co., Ltd., Suzhou, China) and silica gel self-indicator (AR, Tianjin Kermel Chemical Reagent Co., Ltd., Tianjin) by an atmospheric sampling pump (QC-1B, Beijing Municipal Institute of labor Protection, Beijing, China) at an airflow of 500 mL/min.…”
Section: Methodsmentioning
confidence: 99%
“…The growth inhibition rate was calculated according to Yang's method 19 = − × inhibition rate (%) (average diameter of control treatment average diameter of experimental treatment) /(average diameter of control treatment) 100 (1) GC-MS Analysis of B. juncea Volatiles. Volatiles from the aboveground part of B. juncea were collected after 8 weeks of growth in the greenhouse through a "push-pull" system previously reported by Berhal et al 20 Briefly, air was pushed through charcoal active powder (AR, Suzhou Xinqing Technology Co., Ltd., Suzhou, China) and silica gel self-indicator (AR, Tianjin Kermel Chemical Reagent Co., Ltd., Tianjin) by an atmospheric sampling pump (QC-1B, Beijing Municipal Institute of labor Protection, Beijing, China) at an airflow of 500 mL/min. B. juncea tissues (3000g) were placed in a glass chamber (φ = 45 cm, h = 25 cm), and a trap filter made of a glass column and filled with 0.5 g adsorbent material (Porapak Q, 80−100 mesh, Waters), was used to adsorb the volatiles at room temperature.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…It should be noted that the world banana producing countries like Brazil, Ecuador, Uganda, etc. are third world countries and have been documented to experience huge wastages during peaks seasons [31][32][33]. Therefore, bioprocessing would be an alternative pathway for utilization of the un-used or waste bananas into value added products like animal/chicken feeds or fertilizers.…”
Section: Accepted Manuscriptmentioning
confidence: 99%